South vs North : india's great divide - Nilakantan, R.S. (New Delhi : Juggernaut Books, 2022)
In this superbly argued book, data scientist Nilakantan RS shows us how and why the southern states are outperforming the rest of the country and its consequences in an increasingly centralized India. He reveals how south India deals with a particularly tough set of issues - its triumphs in areas of health, education and economic growth are met with a policy regime that penalizes it ; its success in population control will be met with a possible loss of political representation. How will the region manage such an assault? Hard-hitting, troubling and full of fascinating data points, South vs North is an essential book about one of the biggest challenges that India faces today. " -- Amazon
Part I: Taking stock -- 1. Health -- 2. Education -- 3. Economy -- 4. Why has the South performed better? -- Part II: India's wicked problems -- Introduction : is South India an equal partner? -- 1. Population divergence -- 2. India's purse strings : union vs states -- 3. Can the Indian Union be salvaged in its current form? -- Part III: A more perfect union -- Introduction: imagining a better union -- 1. What ails India's representative democracy? -- 2. The Athenian Model -- 3. The alternative.
Includes bibliographical references (pages 267-269).
Keywords: Economic policy; Politics and government; India -- Politics and government -- 21st century; India -- Economics conditions -- 21st century; India -- Economic policy -- 21st century; India